Review of LIDAR-assisted Control for Offshore Wind Turbine Applications. Issue 1 (1st November 2022) - Russell, A. J.; Collu, M.; McDonald, A.; Thies, P. R.; Mortimer, A.; Quayle, A. R.
Abstract : Nacelle-mounted, forward-facing Light Detection and Ranging (LIDAR) technology is able to provide knowledge of the incoming wind so that wind turbines can prepare in advance, through feedforward control. LIDAR can aid in improving wind turbine performance across the full operating range, assisting with torque control in below rated wind speeds, pitch control in above rated wind speeds and yaw control for correctly aligning the turbine rotor with the incoming wind direction. The motivations are for decreasing structural loads, resulting in reduced maintenance and extended lifetimes of turbines and their components, and increasing power capture, both of which can lead to reductions in the levelised cost of energy. This paper provides a review of control strategies that have been employed for LIDAR-assisted turbine control. This paper reviews the computational and practical studies that have been performed for both bottom-fixed and floating turbines and the journey that the field has undertaken since its conceptualisation. Detail is provided of the key differences between fixed and floating offshore turbine dynamics. The paper concludes with guidance for future work within the field, with a focus on floating turbines, as the extent of the literature is scarce when compared to bottom-fixed. Suggestions are offered for how the future studies can better account for the current and future industry landscape. Opportunities for testing of LIDAR-assisted floating turbine control in the field, its benefits for floating substructure design, and the steps needed to be taken to ensure its increased utilisation on industrial projects are also discussed.